2011
DOI: 10.1177/105382590113300302
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Service-Learning: It's Not Always what you Think

Abstract: Service-learning is a teaching strategy that offers students opportunities to learn both in the classroom and in the wider world. This pedagogical tool provides students with chances to directly interact with local agencies and effect change in the community. Thus, service-learning holds the potential to broaden and significantly enhance the learning climate for students. Based on an established theoretical model of academic motivation, the present study examined the effectiveness of service-learning to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 7 publications
2
68
0
9
Order By: Relevance
“…This poses a problem when evaluating how #FunTimesWithTheTA will affect student performance in later courses as one could argue that the more motivated students would outperform their peers, with or without the supplemental lessons. Though we agree with this notion to some extent, we can still evaluate key metrics such as autonomy and competency by following the Basic Psychological Needs Scale [7], [8]. One of the key tenets of #FunTimesWithTheTA is to provide a low-risk, low-stress environment for students to explore new topics within the subject matter to further their own interests.…”
Section: Resultsmentioning
confidence: 99%
“…This poses a problem when evaluating how #FunTimesWithTheTA will affect student performance in later courses as one could argue that the more motivated students would outperform their peers, with or without the supplemental lessons. Though we agree with this notion to some extent, we can still evaluate key metrics such as autonomy and competency by following the Basic Psychological Needs Scale [7], [8]. One of the key tenets of #FunTimesWithTheTA is to provide a low-risk, low-stress environment for students to explore new topics within the subject matter to further their own interests.…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, Colby et al (2009) observed that students gained an in-depth understanding of themselves and their community through community service and service learning. Levesque-Bristol, Knapp, and Fisher (2010) also indicated that service learning contributes to an enhanced learning climate, motivation, civic skills, problem solving, and an appreciation of diversity over the course of a semester. Other studies have concluded that service learning helps students develop valuable professional skills (Bennett, Henson, & Drane, 2003;Lu & Lambright, 2010).…”
Section: What Is Service Learning?mentioning
confidence: 99%
“…Service learning is organized around an academic course or curriculum that provides opportunities for students to interact directly with local agencies to effect change in the community (Levesque-Bristol, Knapp, & Fisher, 2010). Key elements to consider when implementing service learning projects are aligning the goals of the course with the goals of community partners and creating activities that foster student reflection and self-evaluation (Berman, 2006).…”
Section: What Is Service Learning?mentioning
confidence: 99%
“…Using a service learning approach, we then combined students from class with our research in the form of an extra activity to construct an environmental remediation for local lakes. We thought that a service learning approach would be benefi cial because it required students to combine the subject matter within the local context for the betterment of the community (Levesque-Bristol, Knapp, & Fisher, 2010). Th is method also aff orded a new opportunity to describe the processes involved in nutrient cycling of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%